AB0007 Genome-Wide Association Study of Clinical Phenotypes in Psoriatic Arthritis. (15th July 2016) - Cañete, J.; Pinto, J.A.; Gratacos, J.; Queiro, R.; Montilla, C.; Torre-Alonso, J.C.; Perez-Venegas, J.J.; Fernández Nebro, A.; Muñoz, S.; Gonzalez, C.; Roig, D.; Zarco, P.; et al.
Abstract : Background: Genome-wide association studies (GWAS) in Psoriatic Arthritis (PsA)patients and controls have allowed the identification of multiple variants associated with disease risk. To date, however, no GWAS for PsA phenotypes has been reported. Objectives: The main objective of this study was to identify new genetic variation associated with clinical phenotypes in PsA. Methods: A total of n=835 patients diagnosed with PsA using CASPAR criteria were recruited in the discovery stage and genotyped for >600, 000 single nucleotide polymorphisms. GWAS were performed for clinical and biological phenotypes associated with joint and skin disease. After allelic association analysis, those SNPs with highest level of significance were analyzed in an independent cohort of n=414 PsA patients. Results: In the GWAS stage, several genomic regions showing high evidence of association with different PsA phenotypes (P<5e-6) were identified, including axial disease, peripheral disease, bone proliferation, degree of radiological sacroileitis and the presence of syndesmophytes. Also, GWAS on cutaneous phenotypes identified two regions associated with nail disease and skin disease severity. Using the replication cohort, the association between one locus and peripheral pattern, and two loci with axial pattern were validated. Conclusions: Usign a GWAS approach, new loci associated with axial and peripheral disease in PsA have been identified. Disclosure of Interest: None declared